Enteric disease on Operation HERRICK. Issue 3 (27th May 2013) - Connor, Patrick; Hutley, E; Mulcahy, H E; Riddle, M S
Abstract : Background: It is increasingly recognised that diarrhoeal disease is an important contributor to disease non-battle injury (DNBI) rates on operations. Current data collection methods (J97/EPINATO) rely on self-presentation of patients to medical care, which is likely to under-record the true incidence of diarrhoea in theatre. Along with this, the data recording itself is less than adequate, with acknowledged issues in classification of diarrhoeal disease within J97/EPINATO categories. Methods: Two post-tour diarrhoeal disease questionnaire surveillance exercises were carried out at the end of Operation HERRICK 6 (H6) and 10 (H10), respectively. Results: Crude diarrhoeal disease attack rates were similar across the two surveillance periods with approximately 40% of troops questioned reporting at least one diarrhoeal illness episode. The severity of illness increased from H6 to H10 as measured by disease-related symptomatology and days ill and/or off work. Mission burden was substantial and increased in H10 compared with H6. Conclusions: Diarrhoeal disease is a significant cause of DNBI on operations. Current data collection methodologies underestimate its incidence and true operational burden.